Knowledge Criteria for Dental Cavity Material Before, After, and Differences Using Flip Charts for Class V Students of Madrasah Ibtidaiyah Darussalam Ulujami Pesanggrahan District, South Jakarta - RE, Pudentiana Rr; T., Siti Nurbayani; Yulita, Ita; K., Ita Astit; Anggreni, Eka; Lestin (GoAcademica Research & Publishing, 2023)
Tooth cavity disease in Indonesia has a DMF-T index of 4.6 with respective values: Decay component 1.6; Missing component 2.9; and Filling component 0.08; which means tooth decay for the Indonesian population is 460 teeth per 100 people. To reduce the experience index of dental cavities, efforts are being made to increase knowledge (promotional) services so that awareness, motivation, and willingness to change attitudes and behavior in the habit of maintaining dental hygiene increases. After collecting complete data and then processing the statistical analysis, it is hoped that the results will increase the knowledge criteria regarding dental cavities before and after counseling using flip charts for class V students. Researchers used descriptive methods with a cross-sectional design. The data used is primary data using a questionnaire sheet instrument for each respondent, a student at Madrasah Ibtidaiyah Darussalam, Ulujami Village, Pesanggrahan District, South Jakarta. The sample in this study was class V students who were registered as students at Madrasah Ibtidaiyah Darussalam Ulujami, Ulujami Village, Pesanggrahan District, South Jakarta a total of 40 people were divided into 2 groups consisting of 20 people in 1 group or total sampling. The results of the study showed that class V students were given counseling about dental cavities using flip chart print media from initially having poor knowledge criteria (55%) to reaching good knowledge criteria (82.5%) and there was a difference after the intervention to prevent The occurrence of dental and oral diseases in children is therefore a team of dental health workers together with related parties so that services continue and are sustainable in various community groups, including promotive, preventive, curative and rehabilitative efforts and are a very meaningful contribution to the health of the Indonesian people.